Sexual Experiences and Perspectives of Adolescents and Young Adults With Intellectual and Developmental Disabilities. Issue 2 (March 2022) - Schmidt, Elizabeth K.; Dougherty, Megan; Robek, Natalie; Weaver, Lindy; Darragh, Amy R.
The purpose of this study is to understand the sexual experiences and perspectives of adolescents and young adults (AYA) with intellectual or developmental disabilities, how they are receiving sexual education, and how sexual education can be tailored to their needs. This qualitative study utilized semi-structured focus groups and interviews with eight AYA with intellectual or developmental disabilities from January 14 to May 7, 2019. Data were analyzed using a constant comparative approach. Participants reported a diverse range of sexual experiences and an interest in marriage and parenting in the future. Two themes emerged for how AYA are learning about sexual health information: through formal (school, doctors' visits, or from caregivers) and informal education (peers, siblings, self-exploration, or Pop Culture). Sexual education can be tailored to this population by addressing educational gaps (pregnancy, contraception, sexually transmitted infections, intimacy, and sexual activity) and by implementing specific participant recommendations (proactive, inclusive education with real-life examples). With a growing emphasis on disability rights to sexual education among individuals with intellectual or developmental disabilities, it is vital to understand AYA's experiences, perspectives, and current understanding of sexual health information so that we can design a program specifically tailored to meet their unique needs.